2021
DOI: 10.11159/jffhmt.2021.024
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Enhanced Heat Transfer Using a Pair of Similar Porous Baffles in a Backward-Facing Step Flow

Abstract: Baffles have long been known to be useful in enhancing heat transfer in channels with sudden expansions. However, their utility has been limited due to the increased differential pressure they incur in the flow. In this work, a pair of porous baffles is proposed to provide a solution to this problem. It is based on a finite-element numerical simulation of heat transfer and fluid flow through a two-dimensional channel with a backward-facing step. The baffles are modelled as matrices of two-dimensional rods arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…As the adverse pressure gradient decreases, the flow reattaches to the surface. For the case of a BFS channel with no obstacles, the reattachment point is at a distance of five step heights of the step, which is consistent with the results of other studies summarised in [25]. The reattachment point for case 1, located behind the bottom baffle, is slightly closer to the step (X = 4.7).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…As the adverse pressure gradient decreases, the flow reattaches to the surface. For the case of a BFS channel with no obstacles, the reattachment point is at a distance of five step heights of the step, which is consistent with the results of other studies summarised in [25]. The reattachment point for case 1, located behind the bottom baffle, is slightly closer to the step (X = 4.7).…”
Section: Resultssupporting
confidence: 88%
“…His work examined how variations in the height, width, Darcy number, and thermal conductivity of the baffle affect the performance number if the bottom wall temperature was imposed. Arthur and co-workers [24,25] investigated the inclusion of two porous baffles after the step in a BFS channel, one on the bottom wall and other on the top wall, but used a pore-level approach to model the flow through porous media (while Li et al [22] and Zhao [23] used volume-average models). The bottom wall was kept at a constant temperature, and the dimensions and characteristics of the porous baffles were varied, similar to what was done in the works mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…A number of numerical studies have shown the prospect of using porous-like inserts to achieve this purpose at minimal differential pressure cost. However, this has been analysed mostly for laminar flows [1,2]. Studies of turbulent flow with porous inserts in backward-facing step flows are rare [3].…”
mentioning
confidence: 99%